2019
DOI: 10.1038/s41467-019-11293-8
|View full text |Cite
|
Sign up to set email alerts
|

Smu1 and RED are required for activation of spliceosomal B complexes assembled on short introns

Abstract: Human pre-catalytic spliceosomes contain several proteins that associate transiently just prior to spliceosome activation and are absent in yeast, suggesting that this critical step is more complex in higher eukaryotes. We demonstrate via RNAi coupled with RNA-Seq that two of these human-specific proteins, Smu1 and RED, function both as alternative splicing regulators and as general splicing factors and are required predominantly for efficient splicing of short introns. In vitro splicing assays reveal that Smu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 57 publications
3
27
0
Order By: Relevance
“…We identified 11 571 ASEs corresponding to 4570 genes, 14% of which are non-annotated splicing events, that undergo marked (|ΔPSI| ≥ 10%) and significant ( P ≤ 0.05) differential regulation upon depletion of RED ( Supplementary Figure S10B and Supplementary Table S7 ). A clear trend for decreased exon inclusion and increased IR was observed in RED-depleted cells ( Supplementary Figure S10C ), in agreement with previously published studies ( 31 , 32 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We identified 11 571 ASEs corresponding to 4570 genes, 14% of which are non-annotated splicing events, that undergo marked (|ΔPSI| ≥ 10%) and significant ( P ≤ 0.05) differential regulation upon depletion of RED ( Supplementary Figure S10B and Supplementary Table S7 ). A clear trend for decreased exon inclusion and increased IR was observed in RED-depleted cells ( Supplementary Figure S10C ), in agreement with previously published studies ( 31 , 32 ).…”
Section: Resultssupporting
confidence: 92%
“…Poly(A)-tailed RNAs were extracted and subjected to HiSeq2500 Illumina sequencing, and splicing changes induced by RED depletion were analyzed using the same pipeline as described in Figure 1A . PCA indicated that the control siRNA had no effect on splicing and that RED depletion accounted for 45% of the total variance observed in splicing and up to 63% of the total variance observed in the subset of IR events ( Supplementary Figure S10A ), in agreement with the specific requirement of RED–SMU1 for the splicing of short introns ( 31 ). IAV infection accounted for a lower percentage of the variance (16%) along a clearly separate axis.…”
Section: Resultssupporting
confidence: 63%
“…Here we have just described one distinct subset of human SPF45-dependent short introns. Most recently, Smu1 and RED proteins were shown to activate spliceosomal B complexes assembled on human short introns (Keiper et al, 2019). The distance between the 5′ splice site and branch site need to be sufficiently short for Smu1/RED-dependent splicing, whereas in contrast, we clearly showed that this distance per se is not responsible for SPF45-dependent splicing (Figure 2).…”
Section: Discussionmentioning
confidence: 57%
“…Here, we have just described one distinct subset of human SPF45-dependent short introns. Most recently, Smu1 and RED proteins were shown to activate spliceosomal B complexes assembled on human short introns 38 . The distance between the 5′ splice site and branch site need to be sufficiently short for Smu1/RED-dependent splicing, whereas in contrast, we clearly showed that this distance per se is not responsible for SPF45-dependent splicing (Fig.…”
Section: Discussionmentioning
confidence: 99%